Integrated Predictor-Observer Feedback Control for Vibration Mitigation of Large-Scale Spacecraft With Unbounded Input Time Delay - Lyu, Bailiang; Liu, Chuang; Yue, Xiaokui (IEEE transactions on aerospace and electronic systems, 2025)
This research investigates an integrated predictor–observer feedback control strategy for the vibration suppression of large-scale spacecraft affected by unbounded input time-delay effect. The vibration model incorporates orbit-attitude coupling effects, with lumped disturbance introduced to address nonlinearities. Resulted from large-scale characteristics, the unbounded input time-delay is considered during the dynamic response process. Accordingly, for the infinite property of delay effect in time domain, a universal integrated predictor–observer feedback control scheme is developed to achieve asymptotic stabilization of closed-loop system via Lyapunov theory. Notably, the state, disturbance and intermediate observers are analyzed subject to unbounded time-delay respectively to estimate both states and disturbance simultaneously, in contrast to the availability or ignorance assumption directly in existing literature. Then, a predictor is introduced to compensate for the time-delay and prevent adverse performance impacts. Furthermore, numerical simulations of the spacecraft's vibration dynamics are performed to validate the effectiveness of proposed control strategy.